2022
DOI: 10.1038/s44161-022-00021-z
|View full text |Cite
|
Sign up to set email alerts
|

A guide to molecular and functional investigations of platelets to bridge basic and clinical sciences

Abstract: any studies in the past decade have elaborated the emerging functions of platelets beyond hemostasis and thrombosis. Molecular and functional studies have shown diverse roles of platelets in vascular integrity and remodeling, immunoregulation and tissue regeneration (Fig. 1). Although the function of platelets in the development and progression of cardiovascular diseases is well established, platelets were also demonstrated to be critical players in the pathophysiology of cancer, inflammatory diseases and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 174 publications
1
23
0
Order By: Relevance
“…95 Traditional platelet functional assays are reliable, but show very limited potential in clarifying platelet phenotypic heterogeneity and interactions. 96 Considering this in combination with the lack of preexisting knowledge distinguishing the impact of differing SARS-CoV-2 variants on coagulation, and the multifaceted role platelets may play in COVID-19, highlights the need for alertness when approaching research in this uncharted territory. Advancements in techniques such as flow cytometry, electron microscopy, mass spectrometry, and “omics” have started to open up new avenues in platelet research, 96 paving the way for follow-up studies to expand and add to the personalized-based medicine tools presented here.…”
Section: Discussionmentioning
confidence: 99%
“…95 Traditional platelet functional assays are reliable, but show very limited potential in clarifying platelet phenotypic heterogeneity and interactions. 96 Considering this in combination with the lack of preexisting knowledge distinguishing the impact of differing SARS-CoV-2 variants on coagulation, and the multifaceted role platelets may play in COVID-19, highlights the need for alertness when approaching research in this uncharted territory. Advancements in techniques such as flow cytometry, electron microscopy, mass spectrometry, and “omics” have started to open up new avenues in platelet research, 96 paving the way for follow-up studies to expand and add to the personalized-based medicine tools presented here.…”
Section: Discussionmentioning
confidence: 99%
“…However, a normal platelet count is 150–400 × 10 9 /L, suggesting that platelets have another functions (e.g. homeostasis maintenance) other than hemostasis [ 3 , 4 ]. Consistent with this, a series of reports suggested that platelets play a role in physiological responses such as angiogenesis, fibrogenesis, and immune responses [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For analysis, we only employed events of platelets and platelet aggregates. However, we also observed platelets attached to WBCs, which could correspond to platelet-monocyte aggregates whose occurrence is related to platelet activation (18). In a future study, additional staining would allow interpretation of these events, such that including them in the overall analysis could be valuable.…”
Section: Discussionmentioning
confidence: 76%
“…This is consistent with the previous reports that platelets in COVID-19 are highly reactive and have a unique transcriptome profile, and that platelet size and maturity are associated with increased critical illness and all-cause mortality in hospitalized COVID-19 patients (17). Larger platelets are generally at higher risk of forming aggregates and promoting thrombus formation (18). Although there are reports that cardiovascular outcomes are associated with platelet size (19), platelet size was more pronounced in COVID-19 in our analysis.…”
Section: Discussionmentioning
confidence: 99%